Extending the UML for modelling variability for system families - Robak, Silva; Franczyk, Bogdan; Politowicz, Kamil (Zielona Góra: Uniwersytet Zielonogórski)
The process of modelling and developing commonality and variability for system families should be supported by suitable methods and notations. The object-oriented methods and their notations, which are used at present, focus on the development of a single system at a time.
Keywords: object-oriented software engineering; system families; commonality and variability; feature diagram; UML extensibility mechanisms